Business model development of PT Fajar Adhisurya Perkasa - Wenas, Revolt Marthen; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2015)
Abstract.According a report released by Indonesia’s telcommunication firms overall showed strong revenue growth, averaging 6% to 8 % in the second quarter of 2014. Much of that growth can be attribute to BTS firm’s operators success in delivering affordable mobile broadband. Significant increasing in telecommunication industry showing positive impact to PT Fajar Adhisurya Perkasa.In 2015 subscribe in Indonesia will increasing to 391 million and internet increasing from 40 million in 2015 to 178 million in 2016, and business monitor international expects there to be 441.8 million subscribe with penetration rate of 173.8%. In 2011 the Indonesia telecommunication market generated US$ 14.9 billion in service revenue but in the same time PT FASA’s revenue starting decreasing because cost structure strategy. Following the growth of the telecommunication industry, PT Fajar Adhisurya Perkasa’s revenue should be increase significantly. However the cost structures in business model show that company has negative profitability and performance. Its high interest expenses and no prototype, integrity, and low competencies cause PT Fajar Adhisurya Perkasa to suffer from deficit for two years in 2012 and 2013. To increasing its profit and sales, and also to minimize its expenses, PT Fajar Adhisurya Perkasa need to assess the current situations and revise its strategy with business model development to make more appropriate strategy in the future.The new strategy analysis formulation begins with analyzing internal and external environment to identify opportunities and threat of the BTS industry as well as the strengths and weakness of the company. Business model development in part of cost structure and value preposition with create prototype based on project will help company to faster execute project, save money and time in all aspect. The result of all analysis and strategy, company need to restructure cost from external aspect and design prototype for external and internal, applied integrity and competencies to internal’s company.PT Fajar Adhisurya Perkasa needs to consider this strategy to increase revenue, market, profit and make promising sustainable growth in the future. However the company should take urgent actions regarding its financial problem by cutting interest expenses, create prototype, increasing efficiency, and last output with business model development to improve its competitive position.Keyword: Business Model Development, create prototype, BTS Industry